The text of the New Testament in contemporary research: essays on the status quaestionis - Ehrman, Bart D.; Holmes, Michael W. (New Testament tools, studies, and documents, 0077-8842, 2013)
The Text of the New Testament in Contemporary Research: Essays on the Status Quaestionis provides a thoroughly up-to-date assessment of every major aspect of New Testament textual criticism. The twenty-four essays in the volume, all written by internationally acknowledged experts in the field, cover every major aspect of the discipline, discussing the advances that have been made since the mid twentieth century. With full and informative bibliographies, these contributions will be essential reading for anyone interested in moving beyond the standard handbooks in order to see where the discipline now stands, a vade mecum for all students and text-critical scholars for a generation to come